Baryon interactions from lattice QCD with physical masses —S = −3 sector: Ξ∑ and Ξ∑-Λ∑— - Ishii Noriyoshi; Aoki Sinya; Doi Takumi; Gongyo Shinya; Hatsuda Tetsuo; Ikeda Yoichi; Inoue Takashi; Iritani Takumi; Miyamoto Takaya; Nemura Hidekatsu; Sasaki Kenji (EPJ Web of Conferences, 2018)
Hyperon-nucleon and hyperon-hyperon interactions are important in studying the properties of hypernuclei in hypernuclear physics. However, unlike the nucleons which are quite stable, hyperons are unstable so that the direct scattering experiments are difficult, which leads to the large uncertainty in the phenomenological determination of hyperon potentials. In this talk, we use the gauge configurations generated at the (almost) physical point (mπ = 146 MeV) on a huge spatial volume (8:1fm)4 to present our latest result on the hyperon-hyperon potentials in S = −3 sector (Ξ∑ single channel and Ξ∑- ΞΛ; coupled channel) from the Nambu-Bethe-Salpeter wave functions based on the HAL QCD method with improved statistics.